2022
DOI: 10.1111/jgs.18072
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic predictors of individual risk for post‐operative delirium after elective surgery

Abstract: Background Post‐surgical delirium is associated with increased morbidity, lasting cognitive decline, and loss of functional independence. Within a conceptual framework that delirium is triggered by stressors when vulnerabilities exist in cerebral connectivity and plasticity, we previously suggested that neurophysiologic measures might identify individuals at risk for post‐surgical delirium. Here we demonstrate the feasibility of the approach and provide preliminary experimental evidence of the predictive value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The choice of amplitude quantification method also influenced reliability: peak-to-peak was more reliable than the mean of the absolute value (Fig 3K-N), although both had moderate reliability. Our metric for absolute amplitude, the mean of the absolute values within a time window, is equivalent to the common area-under-the-curve (AUC) metrics of TEP amplitude (7,35,67), except with a normalization for window length. Our method for peak-to-peak calculation, similar to that used in (68), differs from some other approaches that rely on temporal peak detection (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of amplitude quantification method also influenced reliability: peak-to-peak was more reliable than the mean of the absolute value (Fig 3K-N), although both had moderate reliability. Our metric for absolute amplitude, the mean of the absolute values within a time window, is equivalent to the common area-under-the-curve (AUC) metrics of TEP amplitude (7,35,67), except with a normalization for window length. Our method for peak-to-peak calculation, similar to that used in (68), differs from some other approaches that rely on temporal peak detection (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested predictive indicators of postoperative delirium. Ross et al discovered that abnormalities in resting-state EEG spectral power or TMS plasticity may indicate a subclinical risk for post-surgery delirium [43]. Lin et al collected 740 patients, 83 of whom developed postoperative delirium, and examined preoperative biochemical markers of cerebrospinal fluid, suggesting that the preoperative α-syn protein level in cerebrospinal fluid can be a predictor of postoperative delirium [44].…”
Section: Discussionmentioning
confidence: 99%
“…Additional applications in future clinical trials include the use of TMS-EEG to predict individualized responses to therapies [69], and to measure subclinical therapeutic responses [70]. It may also be possible for TMS-EEG to predict a patient's risk of delirium [71,72], a common ICU complication.…”
Section: The Clinical Trial Horizonmentioning
confidence: 99%